LEUIT SEBAGAI SIMBOL KEARIFAN LOKAL - Tresnasih, Ria Intani; Lasmiyati, Lasmiyati; Rostiyati, Ani; Merlina, Nina (Paradigma: Jurnal Kajian Budaya, 2023)
Kasepuhan Citorek is centered in Citorek Village, Banten, West Java. The majority of the population are farmers. All harvested produces are only consumed as needed, so the excess rice is stored in a barn called leuit. Rice in leuits can last for more than ten years. This raises the question as to why the rice in leuits can last for so many years. This study aims to find out and explain the customary rules for using crops, the way to store and collect rice to and from leuits, and various aspects related to leuits, i.e. the accompanying traditions, forms, directions, materials, and procedures for making a leuit. This descriptive research used the qualitative approach. Results show that the high durability of rice stored in leuits is due to not only the leuit structure and shape, but also the prevailing rules for planting, harvesting, storing, and taking rice to and from a leuit. Moreover, there are also traditions such as rejecting reinforcements, taboos, and special prayers. In this way, the "correct" treatment and quality of rice are ensured from the start so that the rice stored in a leuit can last for years.